AN ANALYSIS OF TRANSLATION TECHNIQUES USED IN TRANSLATING A SHORT STORY “BEFORE / AFTER” BY MARY MCCLUSKEY - Nurmahalia Dwi Putranti (Journal of English Education Program (JEEP), 2015)
This study is intended to analyze the translation techniques used in translating a short story and the translation techniques mostly used in translating a short story. The translation tehcniques used in this study are adapted from Molina and Albir in 2002. In this regard, two questions are addressed : (1) what are translation techniques used in translating a short story Before / After by Mary McCluskey ? and (2) what is the translation techniques mostly used in translating a short stort Before / After by Mary McCluskey ?. The data were obtained from content analysis. Findings from the content analysis showed the translator used six out of eighteen translation techniques, they are Addition, Borrowing (Pure and Naturalized Borrowing), Literal Translation, Modulation, Reduction, and Transposition. Lastly, the translation techniques mostly used is Literal Translation with total used 33 (34,02%) and the fewest translation techniques used is Pure Borrowing with total used 3 (3,09%).